Kelenteng: Benteng Terakhir Dan Titik Awal Perkembangan Kebudayaan Tionghoa Di Indonesia - M. Herwiratno (Lingua Cultura, 2007)
This article discussed about the degradation of culture among Tionghoa society in Indonesia due to public pressure during Orde Baru era. It is fortune during the hard time, kelenteng as the  place for prayer for Tionghoa society also had became place of protection  for many forms of culture, such as life philosophy, ritual, and art. And now after the political pressure removed and the Tionghoa society wanted to know their culture, kelenteng becomes one of the important sources for knowledge about Tionghua’s culture. But, that apparently was not easy because many kelenteng were in sad condition and being pushed away by the Tionghoa society itself.